Transcriptional regulation of genes throughout the cell cycle - Herrmann, JC (2023)
The mammalian cell cycle is a ubiquitous process intricately linked to development and disease. Unidirectional progression through the cell cycle drivesthe coordinated transcription of hundreds of genes, yet the cis- and trans-regulatory factors involved in this control are incompletely understood. Therefore, the aim of this work was to characterise how genes are transcriptionally regulated throughout the cell cycle and, in particular, whether enhancers are involved in this process. To be able to reproducibly track the cell cycle in a model system, I genetically engineered mouse embryonic stem cells to stably express the Fucci(CA)2 cell cycle reporter system. Using the Fucci(CA)2 signal as ground truth, I identified hundreds of genes with cell cycle-dependent expression, including genes with known cell cycle regulatory roles, as well as gene regulatory networks with cell cycle-dependent activity. Importantly, I found that chromatin accessibility, H3K27ac as a proxy for activity, and the binding of the transcription factor E2f1 are remarkably stable genome-wide throughout the cell cycle. Profiling the cell cycle-resolved regulatory interactions of selected cell cycle-dependent gene promoters using Capture-C revealed that they are similarly invariant. To determine whether the regulatory landscapes of cell cycle genes are cell type-specific, I compared the interaction profiles of the promoters of selected cell cycle genes between mouse embryonic stem and erythroid cells, as well as human erythroid cells at base-pair resolution. I found that the promoters of these genes frequently interact with enhancers in a highly cell type-specific manner, and that these enhancers are often bound by cell type-specific master transcription factors. Lastly, I identified several genes in erythroid cells with conserved interaction profiles between mouse and human. In summary, this work provides initial evidence that enhancers are highly involved in regulating the transcription of genes with functions in a ubiquitous process such as the cell cycle.